2012
DOI: 10.5194/acp-12-10195-2012
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Brewer-Dobson circulation, double tropopauses, ozone and stratospheric water vapour

Abstract: Abstract. Statistical relationships between the variability of the area covered by double tropopause events (DTs), the strength of the tropical upwelling, the total column ozone and of the lower stratospheric water vapour are analyzed. The QBO and ENSO signals in the double tropopause and tropical upwelling as well as their influence on the statistical relationships are also presented. The analysis is based on both reanalysed data (ERA-Interim) and satellite data.Significant anticorrelations were found between… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…Intrusions of tropospheric air into MT regions also have been reported in START08 aircraft campaign data [e.g., Homeyer et al , ]. Castanheira et al [] present a statistical analysis of relationships between the upward branch of the Brewer‐Dobson circulation, the area covered by double tropopauses (DTs), and stratospheric O 3 and lower stratospheric H 2 O. While their statistical results cannot provide direct information on transport pathways, they show correlations between column O 3 , O 3 laminae, wave activity, and areas of DTs that are consistent with those expected from tropical to extratropical transport in the UTLS.…”
Section: Introductionmentioning
confidence: 92%
“…Intrusions of tropospheric air into MT regions also have been reported in START08 aircraft campaign data [e.g., Homeyer et al , ]. Castanheira et al [] present a statistical analysis of relationships between the upward branch of the Brewer‐Dobson circulation, the area covered by double tropopauses (DTs), and stratospheric O 3 and lower stratospheric H 2 O. While their statistical results cannot provide direct information on transport pathways, they show correlations between column O 3 , O 3 laminae, wave activity, and areas of DTs that are consistent with those expected from tropical to extratropical transport in the UTLS.…”
Section: Introductionmentioning
confidence: 92%
“…Castanheira et al [] found that as the baroclinicity in the UTLS increases, a potential outcome of climate change [e.g., Garcia and Randel , ; Randel et al , ], so does the DT frequency. Subsequent studies showed that the meridional extent of the DT is strongly correlated with baroclinic Rossby waves [ Castanheira and Gimeno , ] along with upwelling in the tropics and the frequency of low ozone lamina in the lower stratosphere [ Castanheira et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Peevey et al [] have documented similar results using 3 years (2005–2007) of high‐resolution dynamics limb sounder (HIRDLS) data. Although the formation and maintenance of multiple tropopause system are still not completely understood, increasing evidence points to Rossby wave dynamics as playing an important role in the occurrence of multiple tropopauses [ Pan et al , ; Castanheira and Gimeno , ; Castanheira et al , ; Peevey et al , ].…”
Section: Introductionmentioning
confidence: 99%